2016
DOI: 10.1093/jisesa/iew069
|View full text |Cite
|
Sign up to set email alerts
|

How Does Dung Beetle (Coleoptera: Scarabaeidae) Diversity Vary Along a Rainy Season in a Tropical Dry Forest?

Abstract: Dung beetle community dynamics are determined by regional rainfall patterns. However, little is known about the temporal dynamics of these communities in tropical dry forests (TDFs). This study was designed to test the following predictions: 1) Peak diversity of dung beetle species occurs early in the wet season, with a decrease in diversity (α and β) and abundance throughout the season; 2) Nestedness is the primary process determining β-diversity, with species sampled in the middle and the end of the wet seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 27 publications
1
14
0
1
Order By: Relevance
“…Seasonality did not significantly influence the carabid beetle assemblage, even though numerous studies have shown seasonality to be important in dry forest beetles (e.g., Novais et al 2016;Pérez and Zaragoza 2016;Rangel-Acosta and Martínez-Hernández 2017;Noguera et al 2018). However, there are exceptions; for example dung beetle richness differences between wet and dry seasons in the Caatinga forest in Brazil were small (Medina and Lopes 2014).…”
Section: Discussionmentioning
confidence: 79%
“…Seasonality did not significantly influence the carabid beetle assemblage, even though numerous studies have shown seasonality to be important in dry forest beetles (e.g., Novais et al 2016;Pérez and Zaragoza 2016;Rangel-Acosta and Martínez-Hernández 2017;Noguera et al 2018). However, there are exceptions; for example dung beetle richness differences between wet and dry seasons in the Caatinga forest in Brazil were small (Medina and Lopes 2014).…”
Section: Discussionmentioning
confidence: 79%
“…A dichotomic seasonal (transition between rainy and dry seasons) pattern differentiated by precipitation, has been observed in tropical regions for various groups of insects (Kishimoto-Yamada & Itioka, 2015; Novais et al, 2016) and for different families of beetles in the TDF (Toledo-Hernández et al, 2015; Macedo-Reis et al, 2016; Corona-López et al, 2017; Novais et al, 2018b). For the Cerambycidae communities, this pattern has been recognized in the TDF of different regions of Mexico (Noguera et al, 2002; Noguera et al, 2007; Noguera et al, 2009; Noguera et al, 2012; Toledo et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Insect phenology has been studied in different ecosystems, including environments with little climatic seasonality such as tropical humid forests, and there are more studies in environments that present a marked differentiation between the rainy and dry periods (Wolda, 1988; Zaragoza-Caballero et al, 2010; Novais et al, 2016). The seasonal pattern of insects depends on both the taxonomic group and the environment it inhabits (Kishimoto-Yamada & Itioka, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Las poblaciones de H. achamas y U. coarctatus presentaron una marcada estacionalidad, registrando las mayores abundancias en la época de lluvias, lo cual coincide con lo encontrado para la mayoría de los ensambles de escarabajos coprófagos que presentan cambios estacionales marcados (Peck y Forsyth, 1982;Janzen, 1983, Edwards, 1991Hanski y Cambefort, 1991;Davis, 1993;Boonrotpong et al, 2004;Novais et al, 2016) respondiendo directamente a la precipitación (Andresen, 2005) y donde la severidad de la estación seca ocasiona una fuerte disminución en la actividad de la mayoría de las especies (Hanski y Cambefort, 1991). La actividad de los escarabajos coprófagos se ve restringida a determinados picos de humedad y temperatura que condicionan su fisiología (Halffter y Montes de Oca, 1995).…”
Section: Discussionunclassified